Research on Business Environment Risk Governance Based on Occupational Claims: 1784 Cases of Food Safety Disputes - Jiangjie Sun; Yufei Gao; Xueli Jiang; Yan Li; Mengyao Yang; Ziyan Zhao; Hangzhou Yang; Jinliang You (Complexity)
There are disputes on the legal acceptance of occupational claims and the risk of occupational claim spoiling business environment is skyrocketing. How to manage the risk of occupational claims in the business environment is the subject of urgent research, especially COVID-19 is ravaging the world and the risk of economic crisis is increasing dramatically. In this study, we collected 1784 cases of food occupational claims from the Chinese legal documents website. Using Excel, Review Manager 5.0 and SPSS 19.0, the number of cases prosecuted as “consumers” were obtained by means of textual analysis, and the development process was directly influenced by occupational claims, with 2017 as a great value point (watershed); the rate of losing occupational claim cases has been climbing since 2018; and the risk of losing occupational claims is higher than that of true meaningful consumer advocacy cases (Z = 6.99, p < 0.001), and in 2019, the risk of losing a case was 33.34 times higher than that of an ordinary consumer. The proportion of occupational claims in the total number of food safety disputes is positively correlated with official protective behavior; the failure rate of occupational claims is positively correlated with official regulatory behavior. The results show that occupational claims are being reexamined by society; the continued rise in the number of unsuccessful occupational claims cases indicates a lack of regulatory guidance for their profit-making behavior, the existence of malicious reporting complaints against business behavior, damage to the business environment, and a certain lack of legality. Therefore, it is proposed that laws and regulations should be in line with international standards, highlight the legal thinking and the concept of the rule of law, return to the original legislative intent, and build a five-in-one mechanism of “consumers, operators, media, government, and justice” to coordinate the management of occupational claims, crack down on occupational claims, and contribute to the creation of a good business environment.